If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6x + -9 = 30 Reorder the terms: -9 + 7x + 6x = 30 Combine like terms: 7x + 6x = 13x -9 + 13x = 30 Solving -9 + 13x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 13x = 30 + 9 Combine like terms: -9 + 9 = 0 0 + 13x = 30 + 9 13x = 30 + 9 Combine like terms: 30 + 9 = 39 13x = 39 Divide each side by '13'. x = 3 Simplifying x = 3
| -7y-6=-6y-8 | | x^2+156x+3559=0 | | x^2+156x+355=0 | | 2y+(x-0.5)=23.5 | | 5cos^2t-1= | | 7x-x-3x+x= | | y+8=7 | | y=7.36x-14354.33 | | -2x-2=11z-15 | | C=0.05+4.95 | | 5(t-3)=19 | | x(2x+3)=0 | | 10x=19-(-1) | | 3sin^2t+3cos^2t= | | 2=1+5k | | 4(c+6)=3c-6 | | 5x+102=10x-8 | | 57=9x+7-4x | | 5(g-2)+g=6-1 | | 28y=4 | | F(x)=5x^4-9x^3-7x^2+9x+2 | | 12x^2-2-6=0 | | M+6(m-1)=7 | | 1x+5y=2920 | | X+4=99 | | 5c-40=575 | | 1-4=-6x-3x | | -6n+15=3(n+1) | | x^3-5x^2-8x+8=0 | | -6x-3x=1-4 | | 4(8-2)= | | x^3+6x^2+3=0 |